Pengembangan Sistem Informasi Monitoring Dan Pelaporan Kinerja Karyawan Perusahaan Menggunakan Balanced Scorecard Dan Scrum - Dede Kurniadi; Ridwan Setiawan; Gelar Panca Ginanjar (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This research aims to develop a website-based information system for monitoring and reporting company employee performance to assist companies in managing employee performance appraisals. This research case study was conducted in a company engaged in home marketing in Garut Regency, West Java, Indonesia. The system development is carried out by applying the Balanced Scorecard (BSC) method to evaluate employee performance based on four perspectives: financial perspective, customer perspective, internal business process perspective, learning, and growth perspective. In contrast, the software development methodology uses Agile with the Scrum approach with four stages: requirements, product backlog, sprint planning, sprint, and sprint review. The modeling used in system design is the Unified Modeling Language (UML), then for testing the system software using the BlackBox testing method. The results of this study are a website-based information system for monitoring and reporting company employee performance that companies can use for monitoring and managing employee performance appraisals and displaying information on the results of each employee's performance appraisal.